P80 Patient characteristics and outcomes in a 'Hub and Spoke Model' for liver transplantation provision: The South West Liver Unit/King's College Experience. (6th September 2011) - Petrova, M; Fung, M; Cramp, M E; Mitchell, J D; Cross, T J S
Abstract : Introduction: Liver transplantation (LTx) is the only curative therapeutic modality for patients with end-stage liver disease (ESLD). A detailed evaluation of the liver transplant patient is critical to identify patients most likely to benefit from LTx in an era of organ donor shortage to optimise use of a scarce resource. Aim: The aim of this study was to analyse the profile and outcome of LTx referrals in a 'hub and spoke' LTx service. Method: A retrospective study of all patients referred to the South West Liver Unit, liver transplant service between April 2007 and April 2011. Patients with acute liver failure were excluded from the analysis. Pre-transplant and post-operative follow-up was performed at the South West Liver Unit. All operations were performed at King's College Hospital, London. Pre-LTx demographic and laboratory data were analysed using descriptive methods. Comparisons (Mann–Whitney) and survival (Kaplan–Meier) were estimated. α level of 0.05 was accepted as significant. Results: 191 consecutive patients (n=128, 67% males) underwent elective pretransplant assessment and posttransplant management. Mean age was 53 years, SD 10.3 (range 19–70). Currently, 9.4% (18/191) patients are under assessment, 10.5% (20/191) are on the waiting list for LTx, 29.8% (57/191) have been transplanted, 7.9% (15/191) died on the list and 42.4% (81/191) were assessed but not listed (too advanced disease in 12%, not fulfilling minimal listing criteria 14.7% and contraindicated 15.7%). Among patients who met minimal listing indications 21% (n=19) were diagnosed with hepatocellular carcinoma (chronic HCV infection or/and alcohol background), 30% (n=28) had alcoholic liver disease, 9% (n=8)—chronic HCV infection, 11% (n=10) exhibit both alcohol and viral aetiology, 4% (n=4)—autoimmune hepatitis, 11% (n=10) - PBC/PSC, 4% NASH (n=4), 2% (n=2) cryptogenic cirrhosis and in 9% (n=8) rare diseases (vascular, metabolic, congenital or chronic rejection). These proportions did not deviate from the whole assessed cohort. Mean UKELD, MELD and CTP scores of all assessed patients were 52 (SD 5.2), 12 (SD 5.6) and 8 (SD 1.9). UKELD correlated strongly with MELD and CTP (Spearman's ρ 0.68 and 0.72, p<0.01) and was slightly higher in listed for LTx group. CTP score did not differ between transplanted and not transplanted patients. Among the liver recipients 36% were blood group A, 12% B, 10% AB and 42% O, similar to the distribution in the whole group. Mean BMI was 26.2, not different between transplanted and not listed patients. However, a third of all assessed patients had severe protein malnutrition, evaluated with hand dynamometry and estimated energy expenditure/intake ratio. The prevalence of HPS and PPH were 9% (11/122) and 3% (4/135) respectively. Three months-, 1- and 3-year survival of the patients and the grafts were 98%/97%/97% and 98%/95%/90%. Abstract P80 figure 1 illustrates the differences in survival of transplanted and not transplanted patients. Conclusion: Graft and patient survival in the 'hub and spoke' model is good. Alcohol and hepatoma are the commonest reasons for listing. Protein malnutrition is common in this patient cohort suggesting improved patient nutrition and early dietician involvement is needed.